The effect of load and sliding speed on the wear rate of a metal-polymer composite containing an Al-Co filler - Mykyta, K.A. (Problems of Tribology, 2026)
The paper presents the results of a study on the tribotechnical behaviour of a polymer composite material based on ultra-high-molecular-weight polyethylene, filled with 25 wt.% of a rapidly quenched binary alloy of the Al–10 wt.% Co system. The relevance of the study is due to the need to improve the wear resistance of tribological joints operating under conditions of intensive wear, high loads, and insufficient lubrication. The aim of the study is to develop a mathematical model describing the influence of sliding speed and applied load on the intensity of linear wear of the composite under dry friction conditions using a disk–pad configuration. The study was carried out using a full factorial experiment and a first-order regression model, which made it possible to quantitatively evaluate the influence of the experimental factors and their interaction. It was established that with increasing load, the intensity of linear wear increases significantly, while the influence of sliding speed is less pronounced and becomes evident in interaction with load. A synergistic effect of the combined action of the investigated factors on the linear wear intensity of the polymer composite was identified. The developed mathematical model was validated using statistical criteria and adequately describes the experimental data. The obtained results can be used to predict the wear resistance of the material and to determine rational operating conditions for tribological joints, thereby improving their durability and reliability